Ocular Disease Classification Using Different Kinds of Machine Learning Algorithms - Mardin Abdullah Anwer; Ghassan Akram Qattan; Abbas Mohamad Ali (Zanco Journal of Pure and Applied Sciences, 2024)
Ocular disease is a term used to describe a wide range of illnesses that affect the eyes and visual system. These diseases can affect one or both eyes and can range from mild to severe. The use of machine learning algorithms to categorize ocular diseases has become an area of interest in the ophthalmology community. This study is to compare the performance of different machine learning algorithms in classifying ocular diseases based on fundus images. The dataset of fundus images of patients diagnosed with different ocular diseases like Cataracts, pathological myopia, glaucoma, age-related macular degeneration, and abnormalities are considered. Ocular Disease Intelligent Recognition (ODIR) has been used. The SeequzeNet and GoogleNet deep learning models with different machine learning algorithms employed in experimental work includes KNN, random forest, support vector machines, logistic regression, and gradient boosting. The performance of each algorithm is evaluated using accuracy, sensitivity, and specificity metrics. The results show that logistic regression outperforms the other algorithms in terms of accuracy, sensitivity, and specificity. The findings of this study suggest that machine learning algorithms, particularly Logistic Regression, can be useful in accurately classifying ocular diseases based on fundus images. Feature extraction using SeequzeNet achieved an accuracy of 71.6%, outperforming GoogleNet's accuracy of 68.2%.